Effect of route of inoculation on replication of avian influenza virus (H9N2) and interferon gene expression in guinea fowl (Numida meleagridis). Issue 4 (3rd July 2016) - Umar, S.; Munir, M. T.; Kaboudi, K.; Rehman, A.; Asif, S.; Usman, M.; Ali, A.; Shahzad, M.; Subhan, S.; Shah, M. A. A.
Abstract: The study was designed to investigate the replication of a re-assortant H9N2 avian influenza virus (AIV) and induction of the interferon ( IFNγ ) response after aerosol or intranasal inoculation with the virus in guinea fowl. To determine virus shedding pattern, oropharyngeal and cloacal swabs and tissue specimens of trachea, lungs, spleen and caecal tonsils were collected post-inoculation (pi). Infected guinea fowl showed mild clinical signs, while negative control guinea fowl remained healthy and active throughout the experiment irrespective of the inoculation route. However, the clinical signs were more prominent in guinea fowl infected through the aerosol route. Virus was detected in all oropharyngeal and cloacal swabs up to 7 d pi in guinea fowl from both inoculation groups. However, virus was detected more frequently and in higher titres in oropharyngeal swabs and specimens of trachea and lungs from the group exposed to aerosols than in the group given intranasal drops. In accordance with viral replication findings, expression of IFNγ was up-regulated on 1, 2 and 4 d pi to a significantly higher level in lung tissue specimens from the group exposed to virus aerosol than from controls treated with PBS intranasally. On the other hand, IFNγ was up-regulated above that of controls in lung tissue specimens from the group treated with intranasal drops of virus only on 4 d pi. These findings indicate that virus administered in aerosols was more efficient in infecting the lower respiratory tract and in inducing activity of the IFNγ gene than virus administered as intranasal drops. The results of this study suggest that virus aerosols cause more intense respiratory infection and increase the shedding of the H9N2 AIV in guinea fowl, highlighting the potential role of guinea fowl as a mixing bowl for transmission and maintenance of H9N2 AIV between poultry premises.